Coincident helminth infection modulates systemic inflammation and immune activation in active pulmonary tuberculosis. - Parakkal Jovvian George; Nathella Pavan Kumar; Rathinam Sridhar; Luke E Hanna; Dina Nair; Vaithilingam V Banurekha; Thomas B Nutman; Subash Babu (PLoS Neglected Tropical Diseases, 2014)
Helminth infections are known to modulate innate and adaptive immune responses in active and latent tuberculosis (TB). However, the role of helminth infections in modulating responses associated with inflammation and immune activation (reflecting disease activity and/or severity) in TB is not known.We measured markers of inflammation and immune activation in active pulmonary TB individuals (ATB) with co-incidental Strongyloides stercoralis (Ss) infection. These included systemic levels of acute phase proteins, matrix metalloproteinases and their endogenous inhibitors and immune activation markers. As a control, we measured the systemic levels of the same molecules in TB-uninfected individuals (NTB) with or without Ss infection.Our data confirm that ATB is associated with elevated levels of the various measured molecules when compared to those seen in NTB. Our data also reveal that co-incident Ss infection in ATB individuals is associated with significantly decreased circulating levels of acute phase proteins, matrix metalloproteinases, tissue inhibitors of matrix metalloproteinases as well as the systemic immune activation markers, sCD14 and sCD163. These changes are specific to ATB since they are absent in NTB individuals with Ss infection.Our data therefore reveal a profound effect of Ss infection on the markers associated with TB disease activity and severity and indicate that co-incidental helminth infections might dampen the severity of TB disease.